Elatostema tiechangense (Urticaceae), a new cave-dwelling species from Yunnan, China - Fu, Long-Fei; Monro, Alex K.; Huang, Shi-Lian; Wen, Fang; Wei, Yi-Gang (Phytotaxa, 2017)
Elatostema tiechangense L.F. Fu, Y.G. Wei & A.K. Monro, a new cave-dwelling species from Yunnan, China is described and illustrated. E. tiechangense is most similar to E. quinquecostatum and E. nanchuanense from which it differs by the stem not being sulcate, the pubescent staminate bracts, the smaller and pubescent staminate receptacle, and the suborbicular, smaller pistillate receptacle. A Global Species Conservation Assessment finds that E. tiechangense is endangered (EN) with extinction.